Iron-silicon magnetic material as well as preparation method and application thereof

By passivating and covering the ferrosilicon magnetic powder multiple times, the problems of high core loss and serious heat generation of ferrosilicon magnetic powder are solved, and the high density, low loss and excellent magnetic properties of the material are achieved, and it is suitable for low-frequency electronic components.

CN119480406AActive Publication Date: 2025-02-18HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411742760.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing ferrosilicon magnetic powder core has high loss and severe heat generation, which limits its large-scale application in electronic components.

Method used

By mixing the ferrosilicon magnetic powder with a passivating agent for one heat treatment, and adding the first and second coating agents to the passivating magnetic powder for multiple heat treatments and pressing, a ferrosilicon magnetic material with excellent magnetic properties is formed.

Benefits of technology

It improves the density and effective magnetic permeability of ferrosilicon magnetic materials, reduces losses and heat generation, enhances DC superposition performance, and is conducive to the energy saving and efficiency of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162897020000101
    Figure BDA0005162897020000101
  • Figure BDA0005162897020000111
    Figure BDA0005162897020000111
Patent Text Reader

Abstract

The invention belongs to the technical field of soft magnetic material preparation, and particularly relates to an iron-silicon magnetic material and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing iron-silicon magnetic powder with a passivator, and cooling to room temperature at a speed of not higher than 30 DEG C / h after primary heat treatment; (2) mixing the magnetic powder obtained in the step (1) with a passivating agent to obtain passivated magnetic powder; (3) adding a first coating agent into the passivated magnetic powder to carry out primary coating and secondary heat treatment; (4) adding a second coating agent into the magnetic powder obtained in the step (3) to carry out secondary coating, pressing and third heat treatment; the average particle size of the first coating agent is 300 nm to 1 [mu] m; the second coating agent comprises colloidal particles, and the average particle size of the colloidal particles is not higher than 100 nm. According to the preparation method, the density and effective magnetic conductivity of the iron-silicon magnetic material can be improved, the iron-silicon magnetic material has excellent magnetic performance, loss is greatly reduced, heat is reduced, and energy conservation and high efficiency of devices are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic material preparation, and specifically relates to an iron silicon magnetic material and a preparation method and application thereof. Background Art

[0002] With the development of science and technology, various types of soft magnetic powder cores are widely used in new energy, electrical, communication, automotive industry and other fields, requiring various types of soft magnetic powder cores to develop in the direction of miniaturization, intelligence, high integration, low loss, etc. At present, there are mainly various types of soft magnetic powder cores on the market, such as iron powder cores and metal magnetic powder cores. Among them, iron powder cores have high saturation magnetic induction intensity and low resistivity. They are usually used in low frequency bands and have large eddy current losses at high frequencies. Although the loss of metal magnetic powder cores is greatly reduced compared with that of iron powder cores, the DC superposition characteristics and high-frequency losses still limit their large-scale application. At present, the main metal magnetic powder cores used are iron silicon magnetic powder cores. Although iron silicon magnetic powder cores have low cost and high DC superposition performance, they have high losses and serious heat generation, which is not conducive to energy saving and high efficiency of devices. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art iron silicon magnetic powder core such as high loss and severe heat generation, thereby providing an iron silicon magnetic material and its preparation method and application.

[0004] To this end, the present invention provides the following technical solutions.

[0005] The present invention provides a method for preparing an iron silicon magnetic material, comprising the following steps:

[0006] (1) The iron silicon magnetic powder is mixed with the passivating agent, and after a heat treatment, the mixture is cooled to room temperature at a cooling rate of no more than 30°C / h;

[0007] (2) mixing the magnetic powder obtained in step (1) with a passivating agent to obtain passivated magnetic powder;

[0008] (3) adding a first coating agent to the passivated magnetic powder for primary coating and secondary heat treatment;

[0009] (4) adding a second coating agent to the magnetic powder obtained in step (3) to perform secondary coating, pressing, and heat treatment three times;

[0010] The average particle size of the first coating agent is 300nm-1μm; the second coating agent comprises colloidal particles, and the average particle size of the colloidal particles is not higher than 100nm.

[0011] In an optional embodiment, the difference between the average particle diameters of the colloidal particles in the first coating agent and the second coating agent is 200 nm-1000 nm.

[0012] In an optional embodiment, in step (1), the iron silicon magnetic powder is atomized iron silicon magnetic powder;

[0013] The mass ratio of the iron silicon magnetic powder to the passivating agent is 100:(0.1-0.5); and / or,

[0014] The passivating agent includes at least one of phosphoric acid and aluminum dihydrogen phosphate.

[0015] Optionally, in step (1), the particle size of the atomized iron silicon magnetic powder is 10 μm-40 μm.

[0016] In an optional embodiment, the temperature of the primary heat treatment is 650°C-800°C, and the time is 2h-3h. Optionally, when performing the step (1), the primary heat treatment atmosphere can be any atmosphere of vacuum, nitrogen or argon, which is not specifically limited in the present invention.

[0017] In an optional embodiment, in step (2), the passivating agent includes at least one of phosphoric acid and aluminum dihydrogen phosphate; and / or,

[0018] The amount of the passivating agent used is 0.1wt%-1wt% of the magnetic powder obtained in step (1).

[0019] Optionally, the step (2) of mixing further comprises the step of adding a solvent, the solvent may be but is not limited to at least one of water, acetone and ethanol, and there is no requirement for the amount of solvent, as long as it can completely soak the magnetic powder. Before obtaining the passivated magnetic powder, a drying step is also included.

[0020] In an optional embodiment, in step (3), the first coating agent comprises an organic silicone resin; and / or,

[0021] The amount of the first coating agent is 0.1wt%-1wt% of the passivated magnetic powder obtained in step (2); and / or,

[0022] The temperature of the secondary heat treatment is 300° C.-550° C., and the time is 1 h-2 h.

[0023] In the step (3), the first coating agent includes an organic silicone resin; the first coating agent plays a role of bonding and insulation. In the step (3), when performing the first coating, the step also includes the step of adding a solvent, the solvent has a lower boiling point, the solvent can be but is not limited to at least one of acetone and ethanol, there is no requirement for the amount of solvent, as long as it can completely soak the magnetic powder. After the first coating, the steps of drying and sieving are also included, and the mesh size of the sieving is 80-140 mesh. After the secondary heat treatment, the step of sieving is also included, and the mesh size of the sieving is 80-140 mesh.

[0024] In an optional embodiment, in step (4), the second coating agent is an insulating glue; and / or,

[0025] The amount of the second coating agent added is 1wt%-2wt% of the magnetic powder obtained in step (3).

[0026] In an optional embodiment, the pressing pressure is 1500MPa-2000MPa; and / or,

[0027] The temperature of the three heat treatments is 680° C.-720° C., and the time is 1 h-2 h.

[0028] It should be noted that in step (4), the insulating adhesive comprises 45-80wt% silica sol, 0.1-3wt% silane coupling agent and 20-55wt% polyurethane; the preparation method of the insulating adhesive comprises mixing silica sol, silane coupling agent and polyurethane to form colloidal particles to obtain an insulating adhesive. The average particle size of the colloidal particles is preferably not higher than 20nm. Furthermore, the solid content of the insulating adhesive is 55%-75%. The present invention uses colloidal particles with an average diameter of not more than 100nm for secondary coating, which can better adsorb the particles on the surface of the magnetic powder, increase the insulation effect and reduce the loss.

[0029] The invention provides a ferrosilicon magnetic material obtained by the above preparation method.

[0030] The present invention provides an electronic component, comprising the ferrosilicon magnetic material prepared by the above preparation method.

[0031] The ferrosilicon magnetic material of the present invention can be used as a key material for electronic components (such as transformers, inductors, etc.), and can effectively store and release electromagnetic energy. The ferrosilicon magnetic powder of the present invention is mainly used in electronic components used at low frequencies.

[0032] The technical solution of the present invention has the following advantages:

[0033] 1. The preparation method of the ferrosilicon magnetic material provided by the present invention comprises: (1) mixing ferrosilicon magnetic powder with a passivator, cooling to room temperature at a cooling rate of no more than 30°C / h after a heat treatment; (2) mixing the magnetic powder obtained in the step (1) with a passivator to obtain a passivated magnetic powder; (3) adding a first coating agent to the passivated magnetic powder for a first coating, and a second heat treatment; (4) adding a second coating agent to the magnetic powder obtained in the step (3) for a second coating, pressing, and a third heat treatment; the average particle size of the first coating agent is 300nm-1μm; the second coating agent contains colloidal particles, and the average particle size of the colloidal particles is no more than 100nm. The preparation method can improve the density and effective magnetic permeability of the ferrosilicon magnetic material, so that the ferrosilicon magnetic material has excellent magnetic properties, greatly reduces losses, reduces heat generation, is conducive to energy saving and high efficiency of the device, and also has high DC superposition performance. When preparing magnetic materials, uneven coating will cause the eddy current loss of magnetic powder to increase. The particle size of the first coating agent is larger than that of the second coating agent. Large particles are used for coating first, and then small particles are used for filling. The large difference in particle size between the two coating agents can form a more uniform coating and avoid uneven coating of large or small particles, thereby improving insulation performance and reducing losses.

[0034] When preparing magnetic materials, the present invention first passivates the iron silicon magnetic powder twice to make the surface passivation of the magnetic powder more uniform, which is beneficial to the subsequent insulation coating effect and allows the silicon particles to better adhere to the surface of the magnetic powder. After the first passivation is completed, the temperature is lowered to room temperature at a rate not higher than 30°C / h, which can better release the internal stress of the magnetic powder and help improve the material performance. The passivated magnetic powder is coated for the first time and then subjected to a secondary heat treatment, which can volatilize other substances in the silicone resin and reduce impurities. Only silicon particles are coated on the surface of the magnetic powder, which has the effect of bonding and insulation, and prepares for the second coating. The second coating can fill or repair the gaps that appear during the first coating, so that the silicon particles on the surface of the magnetic powder are more evenly distributed, achieving a better insulation effect, thereby reducing the loss of the magnetic powder; the third treatment is the treatment after the magnetic powder is pressed into a ring, and the debinding takes into account the release of internal stress to obtain a suitable FeSi phase, thereby reducing losses and reducing heat. DETAILED DESCRIPTION

[0035] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0036] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0037] The preparation method of the insulating glue used in the following examples and comparative examples is as follows:

[0038] The preparation method of an insulating adhesive liquid with an average colloidal particle diameter of 20 nm includes: mixing silica sol (manufacturer and model: Zhejiang Yuda Chemical Silica Sol, Z3-20), polyurethane and silane coupling agent in a mass ratio of 65:35:1 to obtain a modified silica sol containing colloidal particles, and the solid content of the modified silica sol is about 60wt%.

[0039] The preparation method of an insulating adhesive liquid with an average colloidal particle diameter of 30 nm includes: mixing silica sol (manufacturer and model: Zhejiang Yuda Chemical Silica Sol, Z3-30), polyurethane and silane coupling agent (KH560) in a mass ratio of 65:35:1 to obtain a modified silica sol containing colloidal particles, and the solid content of the modified silica sol is about 60wt%.

[0040] The preparation method of an insulating adhesive liquid with an average colloidal particle diameter of 50 nm includes: mixing silica sol (manufacturer and model: Zhejiang Yuda Chemical Silica Sol, Z3-50), polyurethane and silane coupling agent (KH560) in a mass ratio of 65:35:1 to obtain a modified silica sol containing colloidal particles, and the solid content of the modified silica sol is about 60wt%.

[0041] The preparation method of an insulating adhesive liquid with an average colloidal particle diameter of 100 nm includes: mixing silica sol (manufacturer and model: Zhejiang Yuda Chemical Silica Sol, Z3-100), polyurethane and silane coupling agent (KH560) in a mass ratio of 65:35:1 to obtain a modified silica sol containing colloidal particles, and the solid content of the modified silica sol is about 60wt%.

[0042] The preparation method of an insulating adhesive liquid with an average colloidal particle diameter of 200 nm includes: mixing silica sol (manufacturer and model: Zhejiang Yuda Chemical Silica Sol, Z3-200), polyurethane and silane coupling agent (KH560) in a mass ratio of 65:35:1 to obtain a modified silica sol containing colloidal particles, and the solid content of the modified silica sol is about 60wt%.

[0043] The purity of phosphoric acid used in the following examples and comparative examples is higher than 99%.

[0044] Example 1

[0045] This embodiment provides a method for preparing an iron silicon magnetic material, comprising the following steps:

[0046] (1) Atomized iron silicon magnetic powder with a particle size of 30 μm was selected, fully mixed with phosphoric acid and placed in a heat treatment furnace. The furnace temperature was raised to 740°C and kept at this temperature for 2 hours, then slowly cooled to room temperature and taken out of the furnace. The cooling rate was 30°C / h, and the atmosphere in the furnace was vacuum. The mass ratio of phosphoric acid to atomized iron silicon magnetic powder was 0.2:100.

[0047] (2) The magnetic powder obtained in step (1) is mixed with phosphoric acid in a mass ratio of 100:0.2, and acetone is added to completely soak the magnetic powder. The mixture is dried at 80° C. while stirring to obtain passivated magnetic powder.

[0048] (3) The passivated magnetic powder and the silicone resin were mixed in a mass ratio of 100:0.5, and the solvent acetone was added to completely soak the magnetic powder, dried naturally, crushed and passed through a 140-mesh sieve, and then placed in a heat treatment furnace, kept at 450°C for 1.5 hours under a nitrogen atmosphere, cooled to room temperature with the furnace, and passed through a 140-mesh sieve to obtain a primary coated magnetic powder. The average particle size of the silicone resin is 400 nm.

[0049] (4) The primary coated magnetic powder is mixed with the modified silica gel liquid at a mass ratio of 100:1, and the solvent acetone is added to completely soak the magnetic powder, naturally dried, and crushed through a 100-mesh sieve to obtain the secondary coated magnetic powder; wherein the average particle size of the colloidal particles in the modified silica gel liquid is 20nm. The secondary coated magnetic powder is fully mixed with the release agent zinc stearate at a mass ratio of 100:0.4 and then placed in a press for molding, with a molding pressure of 1900MPa; then heat treated at 700℃ in a nitrogen atmosphere for 1h, and cooled to room temperature with the furnace to obtain an iron silicon magnetic core.

[0050] Example 2

[0051] This embodiment provides a method for preparing an iron silicon magnetic material, comprising the following steps:

[0052] (1) Atomized iron silicon magnetic powder with a particle size of 30 μm was selected, fully mixed with phosphoric acid and placed in a heat treatment furnace. The furnace temperature was raised to 740°C and kept at this temperature for 2 hours, then slowly cooled to room temperature and taken out of the furnace. The cooling rate was 30°C / h, and the atmosphere in the furnace was vacuum. The mass ratio of phosphoric acid to atomized iron silicon magnetic powder was 0.2:100.

[0053] (2) The magnetic powder obtained in step (1) is mixed with phosphoric acid in a mass ratio of 100:0.2, and acetone is added to completely soak the magnetic powder. The mixture is dried at 80° C. while stirring to obtain passivated magnetic powder.

[0054] (3) The passivated magnetic powder and the silicone resin were mixed in a mass ratio of 100:0.5, and the solvent acetone was added to completely soak the magnetic powder, dried naturally, crushed and passed through a 140-mesh sieve, and then placed in a heat treatment furnace, kept at 450°C for 1.5 hours under a nitrogen atmosphere, cooled to room temperature with the furnace, and passed through a 140-mesh sieve to obtain a primary coated magnetic powder. The average particle size of the silicone resin is 400 nm.

[0055] (4) The primary coated magnetic powder is mixed with the modified silica gel liquid at a mass ratio of 100:1, and the solvent acetone is added to completely soak the magnetic powder, naturally dried, and crushed through a 100-mesh sieve to obtain the secondary coated magnetic powder; wherein the average particle size of the colloidal particles in the modified silica gel liquid is 50nm. The secondary coated magnetic powder is fully mixed with the release agent zinc stearate at a mass ratio of 100:0.4 and then placed in a press for molding at a molding pressure of 1900MPa; then heat treated at 700℃ in a nitrogen atmosphere for 1h, and cooled to room temperature with the furnace to obtain an iron silicon magnetic core.

[0056] Example 3

[0057] This embodiment provides a method for preparing an iron silicon magnetic material, comprising the following steps:

[0058] (1) Atomized iron silicon magnetic powder with a particle size of 30 μm was selected, fully mixed with phosphoric acid and placed in a heat treatment furnace. The furnace temperature was raised to 740°C and kept at this temperature for 2 hours, then slowly cooled to room temperature and taken out of the furnace. The cooling rate was 30°C / h, and the atmosphere in the furnace was vacuum. The mass ratio of phosphoric acid to atomized iron silicon magnetic powder was 0.2:100.

[0059] (2) The magnetic powder obtained in step (1) is mixed with phosphoric acid in a mass ratio of 100:0.2, and acetone is added to completely soak the magnetic powder. The mixture is dried at 80° C. while stirring to obtain passivated magnetic powder.

[0060] (3) The passivated magnetic powder and the silicone resin were mixed in a mass ratio of 100:0.5, and the solvent acetone was added to completely soak the magnetic powder, dried naturally, crushed and passed through a 140-mesh sieve, and then placed in a heat treatment furnace, kept at 450°C for 1.5 hours under a nitrogen atmosphere, cooled to room temperature with the furnace, and passed through a 140-mesh sieve to obtain a primary coated magnetic powder. The average particle size of the silicone resin is 400 nm.

[0061] (4) The primary coated magnetic powder is mixed with the modified silica gel liquid at a mass ratio of 100:1, and the solvent acetone is added to completely soak the magnetic powder, naturally dried, and crushed through a 100-mesh sieve to obtain the secondary coated magnetic powder; wherein, the average particle size of the colloidal particles in the modified silica gel liquid is 100nm. The secondary coated magnetic powder is fully mixed with the release agent zinc stearate at a mass ratio of 100:0.4 and then placed in a press to form the mold at a molding pressure of 1900MPa; then heat treated in a nitrogen atmosphere at 700°C for 1h, and cooled to room temperature with the furnace to obtain an iron silicon magnetic core.

[0062] Example 4

[0063] This embodiment provides a method for preparing an iron silicon magnetic material, comprising the following steps:

[0064] (1) Atomized iron silicon magnetic powder with a particle size of 20 μm was selected, fully mixed with phosphoric acid and placed in a heat treatment furnace. The furnace temperature was raised to 720°C and kept at this temperature for 2 hours, then slowly cooled to room temperature and taken out of the furnace. The cooling rate was 30°C / h, and the atmosphere in the furnace was vacuum. The mass ratio of phosphoric acid to atomized iron silicon magnetic powder was 0.2:100.

[0065] (2) The magnetic powder obtained in step (1) is mixed with phosphoric acid in a mass ratio of 100:0.2, and acetone is added to completely soak the magnetic powder. The mixture is dried at 80° C. while stirring to obtain passivated magnetic powder.

[0066] (3) The passivated magnetic powder and the silicone resin were mixed in a mass ratio of 100:0.7, and the solvent acetone was added to completely soak the magnetic powder, dried naturally, crushed and passed through a 140-mesh sieve, and then placed in a heat treatment furnace, kept at 450°C for 1.5 hours under a nitrogen atmosphere, cooled to room temperature with the furnace, and passed through a 140-mesh sieve to obtain a primary coated magnetic powder. The average particle size of the silicone resin is 500 nm.

[0067] (4) The primary coated magnetic powder is mixed with the modified silica gel liquid at a mass ratio of 100:1, and the solvent acetone is added to completely soak the magnetic powder, naturally dried, and crushed through a 100-mesh sieve to obtain the secondary coated magnetic powder; wherein the average particle size of the colloidal particles in the modified silica gel liquid is 30nm. The secondary coated magnetic powder is fully mixed with the release agent zinc stearate at a mass ratio of 100:0.3 and then placed in a press for molding at a molding pressure of 1800MPa; then heat treated at 700℃ in a nitrogen atmosphere for 1h, and cooled to room temperature with the furnace to obtain an iron silicon magnetic core.

[0068] Example 5

[0069] This embodiment provides a method for preparing an iron silicon magnetic material, which differs from Embodiment 4 in that the annealing temperature in step (3) is 300°C.

[0070] Example 6

[0071] This embodiment provides a method for preparing an iron silicon magnetic material, which differs from Embodiment 4 in that the annealing temperature in step (3) is 500°C.

[0072] Example 7

[0073] This embodiment provides a method for preparing an iron silicon magnetic material, which differs from Embodiment 4 in that the annealing temperature in step (3) is 600°C.

[0074] Example 8

[0075] This embodiment provides a method for preparing an iron silicon magnetic material, comprising the following steps:

[0076] (1) Atomized iron silicon magnetic powder with a particle size of 30 μm was selected, fully mixed with phosphoric acid and placed in a heat treatment furnace. The furnace temperature was raised to 740°C and kept at this temperature for 2 hours. The temperature was then slowly lowered to room temperature and taken out of the furnace. The cooling rate was 15°C / h. The atmosphere in the furnace was vacuum. The mass ratio of phosphoric acid to atomized iron silicon magnetic powder was 0.1:100.

[0077] (2) The magnetic powder obtained in step (1) is mixed with phosphoric acid in a mass ratio of 100:0.4, and acetone is added to completely soak the magnetic powder. The mixture is dried at 80° C. while stirring to obtain passivated magnetic powder.

[0078] (3) The passivated magnetic powder and the silicone resin were mixed in a mass ratio of 100:0.5, and the solvent acetone was added to completely soak the magnetic powder, dried naturally, crushed and sieved with a 140-mesh sieve, and then placed in a heat treatment furnace, kept at 450°C for 1.5 hours under a nitrogen atmosphere, cooled to room temperature with the furnace, and sieved with a 140-mesh sieve to obtain a primary coated magnetic powder. The average particle size of the silicone resin is 500 nm.

[0079] (4) The primary coated magnetic powder was mixed with the modified silica gel liquid at a mass ratio of 100:1.5, and the solvent acetone was added to completely soak the magnetic powder, dried naturally, and crushed through a 100-mesh sieve to obtain the secondary coated magnetic powder; wherein, the average particle size of the colloidal particles in the modified silica gel liquid was 50nm. The secondary coated magnetic powder was fully mixed with the release agent zinc stearate at a mass ratio of 100:0.4 and then placed in a press for molding at a molding pressure of 1900MPa; then heat treated at 700℃ in a nitrogen atmosphere for 1h, and cooled to room temperature with the furnace to obtain an iron silicon magnetic core.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing an iron silicon magnetic material, which is different from Example 1 in that the average particle size of the colloidal particles in the modified silica gel liquid in step (4) is 200 nm.

[0082] Comparative Example 2

[0083] This comparative example provides a method for preparing ferrosilicon magnetic material, which is different from Example 1 in that the average particle size of the organic silicon in step (3) is 100 nm.

[0084] Test example

[0085] This test example provides the performance tests and results of the iron silicon cores of various embodiments and comparative examples.

[0086] During the pressing process, the outer diameter of the pressed magnetic ring is 12.7mm, the inner diameter is 7.6mm, and the height is 3mm. The density of the magnetic core is tested by the drainage method, and then the magnetic core is wound. The inductance L is tested by LCR, and then the effective magnetic permeability μ of the ring magnetic core is calculated. The test frequency is 100kHz. The AC loss of the magnetic core is tested by the Japanese Iwasaki SY-8218 soft magnetic BH analyzer. The test conditions are: 50kHz, 100mT, and temperature is 25℃.

[0087] Table 1 Performance test results of various embodiments and comparative examples

[0088]

[0089]

[0090] It can be seen from the above results that the magnetic core prepared by the present invention has low loss and can prevent the occurrence of severe heating. From Examples 1-3, as the average diameter of the colloidal particles in the modified silica gel liquid increases, the loss tends to be larger. When the average diameter of the colloidal particles is too high, such as when the average diameter of the colloidal particles in Comparative Example 1 increases to 200nm, the magnetic core is unevenly coated and the loss is large, which is not conducive to the magnetic properties of the magnetic core.

[0091] From Examples 4-6, it can be seen that the heat treatment temperature after the first coating is 300-550°C which helps to optimize the loss and magnetic permeability of the magnetic core.

[0092] From Comparative Examples 1-2, the present invention performs a first coating on the passivated magnetic powder and then performs a secondary heat treatment, which can volatilize other substances in the silicone resin and reduce impurities. Only silicon particles are coated on the surface of the magnetic powder, which has the effect of bonding and insulation, and prepares for the secondary coating. The secondary coating can fill or repair the gaps that appear during the first coating, so that the silicon particles on the surface of the magnetic powder are more evenly distributed, achieving a better insulation effect, and thereby reducing the loss of the magnetic powder.

[0093] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing an iron silicon magnetic material, characterized in that: The following steps are involved: (1) The iron silicon magnetic powder is mixed with the passivating agent, and after a heat treatment, the mixture is cooled to room temperature at a cooling rate of no more than 30°C / h; (2) mixing the magnetic powder obtained in step (1) with a passivating agent to obtain passivated magnetic powder; (3) adding a first coating agent to the passivated magnetic powder for primary coating and secondary heat treatment; (4) adding a second coating agent to the magnetic powder obtained in step (3) to perform secondary coating, pressing, and heat treatment three times; The average particle size of the first coating agent is 300nm-1μm; the second coating agent comprises colloidal particles, and the average particle size of the colloidal particles is not higher than 100nm.

2. The preparation method according to claim 1, characterized in that: The difference between the average particle diameters of the colloidal particles in the first coating agent and the second coating agent is 200 nm to 1000 nm.

3. The preparation method according to claim 1 or 2, characterized in that: In the step (1), the iron silicon magnetic powder is atomized iron silicon magnetic powder; The mass ratio of the iron silicon magnetic powder to the passivating agent is 100:(0.1-0.5); and / or, The passivating agent includes at least one of phosphoric acid and aluminum dihydrogen phosphate.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The temperature of the primary heat treatment is 650°C-800°C, and the time is 2h-3h.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step (2), the passivating agent comprises at least one of phosphoric acid and aluminum dihydrogen phosphate; and / or, The amount of the passivating agent used is 0.1wt%-1wt% of the magnetic powder obtained in step (1).

6. The preparation method according to any one of claims 1 to 5, characterized in that: In the step (3), the first coating agent comprises an organic silicone resin; and / or The amount of the first coating agent is 0.1wt%-1wt% of the passivated magnetic powder obtained in step (2); and / or, The temperature of the secondary heat treatment is 300° C.-550° C., and the time is 1 h-2 h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step (4), the second coating agent is an insulating glue; and / or, The amount of the second coating agent added is 1wt%-2wt% of the magnetic powder obtained in step (3).

8. The preparation method according to any one of claims 1 to 7, characterized in that: The pressing pressure is 1500MPa-2000MPa; and / or, The temperature of the three heat treatments is 680° C.-720° C., and the time is 1 h-2 h.

9. The ferrosilicon magnetic material obtained by the preparation method according to any one of claims 1 to 7.

10. An electronic component, characterized in that: The invention comprises a ferrosilicon magnetic material prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Iron-nickel magnetic powder core and preparation method thereof

    CN115762945A

  • Iron-cobalt magnetic powder core and preparation method and application thereof

    CN115881383A

  • Multilayer core-shell structure soft magnetic composite material and preparation method thereof

    CN116543995A

  • Metal magnetic powder core with low magnetic conductivity and low loss as well as preparation method and application of metal magnetic powder core

    CN118658692A

  • Preparation method of soft magnetic powder core material

    CN119028726A